Application of co-pyrolysis biochar for the adsorption and immobilization of heavy metals in contaminated environmental substrates - Li, Yuanling; Yu, Han; Liu, Lina; Yu, Hongbing (Journal of hazardous materials, 2021)
Heavy metal pollution has been considered as a serious threat to the environment and human in the past decades due to its toxic and unbiodegradable properties. Recently, extensive studies have been carried out on the removal of heavy metals, and various adsorption materials have been successfully developed. Among, biochar is a promising option because of its advantages of various biomass sources, abundant microporous channels and surface functional groups, as well as its attractive economic feasibility. However, the application of pristine biochar is limited by its low adsorption capacity and nonregenerative property. Co-pyrolysis biochar, produced from the pyrolysis of biomass with the addition of another biomass or non-biomass precursor, is potential in overcoming the limitation of pristine biochar and achieving superior performance for heavy metal adsorption and immobilization. Therefore, this article summarizes the recent advances in development and applications of co-pyrolysis biochar for adsorption and immobilization of various heavy metals in contaminated environmental substrates. In details, the production, characteristics and advantages of co-pyrolysis biochar are initially presented. Subsequently, the adsorption behaviors and mechanisms of different heavy metals (including Hg, Zn, Pb, Cu, Cd, Cr, As, etc.) in flue gas and wastewater by co-pyrolysis biochar are reviewed, as well as factors influencing their adsorption capacities. Meanwhile, the immobilization of heavy metals in both biochar itself and contaminated soils by co-pyrolysis biochar is discussed. Finally, the limitations of current studies and future prospects are proposed. It aims at providing a guideline for the exploitation and application of cost-effective and environmental-friendly co-pyrolysis biochar in the decontamination of environmental substrates. [Display omitted] •Co-pyrolysis biochar is more capable in heavy metal removal than pristine biochar.•Adsorption mechanism of various heavy metals by co-pyrolysis biochar is summarized.•Factors influencing heavy metal adsorption by co-pyrolysis biochar are discussed.•Heavy metal immobilization in both co-pyrolysis biochar and soils is elucidated.•Future prospects are proposed in heavy metal removal by co-pyrolysis biochar.